A genus at risk: Predicted current and future distribution of all three Lagopus species reveal sensitivity to climate change and efficacy of protected areas. Issue 9 (2nd July 2021) - Scridel, Davide; Brambilla, Mattia; de Zwaan, Devin R; Froese, Nick; Wilson, Scott; Pedrini, Paolo; Martin, Kathy
Abstract: Aim: Cold‐adapted species are considered vulnerable to climate change. However, our understanding of how climate‐induced changes in habitat and weather patterns will influence habitat suitability remains poorly understood, particularly for species at high latitudes or elevations. Here, we assessed potential future distributions for a climate‐sensitive genus, Lagopus, and the effectiveness of protected areas in tracking shifting distributions. Location: British Columbia, Canada. Methods: Using community science observations from 1970 to 2020, we built species distribution models for white‐tailed ( L. leucura ), rock ( L. muta ) and willow ptarmigan ( L. lagopus ) across British Columbia, a globally unique region harbouring all three ptarmigan species. We assessed the impact of climate (direct) and climate‐induced habitat change (indirect) on potential future distributions of ptarmigan. Results: White‐tailed and rock ptarmigan were associated with colder temperatures and tundra‐like open habitats and willow ptarmigan with open, shrub habitats. Future projections based on climate and vegetation scenarios indicated marked losses in suitable habitat by the 2080s (RCP +8.5 W/m 2 ), with range declines of 85.6% and 79.5% for white‐tailed and rock ptarmigan, respectively, and a lower 61.3% for willow ptarmigan. Predicted current and future suitable habitat occurred primarily outside of current protected areas (67%–82%), yet range size declined at a less pronounced rate within protected areas suggesting a capacity to buffer habitat loss. Main conclusions: Ptarmigan are predicted to persist at higher elevations and latitudes than currently occupied, with the magnitude of elevation shifts consistent with trends observed elsewhere in the Holarctic. Our spatially explicit assessment of potential current and future distributions of ptarmigan species provides the first comprehensive evaluation of climate change effects on the distribution of three congeneric, cold‐adapted species with different habitat preferences and life‐history traits. We also highlight the potential role of protected areas in preserving suitable future sites for ptarmigan and other climate‐sensitive or high‐elevation species. Abstract : Summary of average current and future predictions for shifts in elevation, latitude, and range size for the genus Lagopus in BC. Current and future potential range losses are shown with respect to protected (P) and unprotected areas (U) with size of pie charts being proportional to the relative value of current and future species' range.